Determinants of Intention to Use BYOND by BSI Mobile Banking: The Roles of Perceived Ease of Use, Perceived Usefulness, Service Features, and Perceived Risk - Zakiya Salsabila; Nihayatu Aslamatis Solekah (JPS (Jurnal Perbankan Syariah), 2026)
Purpose - This study aims to analyze the effect of perceived ease of use, perceived usefulness, service features, and perceived risk on the intention to use BYOND by BSI mobile banking in Malang City. Methodology - This research employs a quantitative approach using a survey method, where primary data were collected through questionnaires distributed to 125 respondents who are active users of BYOND by BSI mobile banking in Malang City. The sample was selected using a non-probability sampling technique with purposive sampling method. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3, including outer model evaluation through Confirmatory Factor Analysis (CFA) and inner model analysis for hypothesis testing. Findings - The results indicate that perceived ease of use, perceived usefulness, and service features have a positive and significant effect on the intention to use BYOND by BSI mobile banking in Malang City. Meanwhile, perceived risk does not have a significant effect on usage intention. Implications - These findings suggest that enhancing ease of use, perceived benefits, and service feature quality plays an important role in increasing users’ intention to adopt mobile banking services, while perceived risk is not a determining factor in this context.